Meningkatkan Kompetensi Profesional Melalui Pelatihan Penyusunan Modul Ajar Untuk Pendidik PAUD - Mutoharoh, Mutoharoh; Nadifah, Robiatun; Hadijah, Hadijah; Triyastati, Satriyah; Rumdanah, Rumdanah; Hayati, Witoh; Fatmawati, Ifat; Khodanah, Khodanah; Mariyah, Iim; Fuadah, Hanis; Islahiyah, Islahiyah; Sulkhah, Sulkhah; Fatimah, Endang (Civiliza Publishing, 2025)
Early Childhood Education (ECE) is a crucial stage in a child's development. The quality of learning in ECE is very important to form the foundation of a child's growth and readiness. One of the main factors that determine the success of learning is the competence of teachers, especially in preparing teaching modules. This study uses a descriptive qualitative method with a participatory approach to improve the competence of ECE teachers in preparing effective and fun teaching modules. The results of the training showed an increase in teachers' understanding of the concept of teaching modules, the ability to prepare more structured and interesting teaching modules, and the implementation of the training that went well and smoothly. This training has a positive impact on improving the competence of ECE teachers in designing more effective and fun learning for early childhood.